PENGARUH TRANSAKSI NON TUNAI MENGGUNAKAN LAYANAN VIRTUAL BISNIS TERHADAP KEPUASAN KONSUMEN PADA PT. INDOMARCO PRISMATAMA CABANG MEDAN - Nurain Harahap (Bisnis-Net, 2018)
This research includes quantitative research. This study aims to test the hypothesis and is a study thatexplains the phenomenon in the form of relationships between variables. The main purpose of this studyis to identify the causal relationship between variables. In this study, researchers wanted to test the effectof non-cash transactions using virtual business to Consumer Satisfaction. The population used in thisstudy is the consumer who ever made a virtual purchase / payment. Sampling method used is nonprobability sampling. While determination of the number of respondents (samples) is done throughaccidental sampling method. So the sample in this study amounted to 20% of the population of 70consumers. Variable Measurement Scale in this study was measured using the Likert Scale. ModelAnalysis of daa used is a simple linear regression analysis model that is to predict the degree of influenceof independent variables on the dependent variable. To test the hypothesis, a Simple Linear RegressionModel is used. The t test result obtained from the output table is 24.24. While ttable 0,24 with Î± = 5%.With thitung> ttable (24,24> 0,24). This means that non-cash transactions using virtual businessservices affect consumer satisfaction at PT. Indomarco Prismatama Medan Branch